High-dose chemotherapy supported with autologous hematopoietic stem cell transplant in small-cell lung cancer - Krzakowski, Maciej (Contemporary Oncology/Współczesna Onkologia, 2006)
Small-cell lung cancer provides clinicians with a paradox. Although it is a highly chemosensitive disease, it remains ultimately fatal for the majority of patients. The majority of patients respond to first-line chemotherapy, but such responses are of relatively short duration. More than 90% of patients die from the disease due to the development of a drug resistance. Escalating the dose of conventional chemotherapy and treatment intensification with autologous bone marrow or peripheral blood stem cell transplant is a theoretical method to overcome the drug resistance. The efficacy of high-dose therapy with stem cells support as an early component of treatment produced the results comparable to those achieved with standard chemotherapy. High-dose therapy with the substitution of peripheral blood stem cells as late intensification after the standard treatment was tested more commonly, particularly in a selected population of younger patients with limited disease, better performance status and less frequent comorbid conditions. Even in this more favourable subset, the survival benefits were not clear despite reduced treatment-related mortality. Up to date, the superiority of an intensified treatment strategy in small-cell lung cancer has not been demonstrated in a convincing way and further controlled trials are necessary to clarify its role, since major problems such as the selection of patients, doses and timing of chemotherapy and radiotherapy remain unsolved. The integration of new molecularly targeted agents into research protocols may be appropriate.